Analysis Of Factors Influencing Blood Glucose Levels And Periodontal Disease In Patients With Diabetes Mellitus - Kai, Meggy Wulandari; Ulfah, Rasuna; Nuryati, Sri (JURNAL CITRA KEPERAWATAN, 2025)
Diabetes mellitus is a chronic, incurable disease associated with a reduced life expectancy of approximately 10 years due to cardiovascular complications such as ischemic heart disease and stroke. According to the International Diabetes Federation and WHO, the number of people with diabetes in Indonesia is projected to rise from 8.4 million in 2000 to 21.3 million in 2030. Data from the 2018 National Basic Health Research (Riskesdas) indicated an increase in prevalence from 6.9% in 2013 to 8.5% in 2018, with higher rates in urban (2.0%) compared to rural (1.0%) areas, and the highest prevalence observed up to the age of 65. South Kalimantan ranks second nationally in periodontal disease prevalence, which is significantly associated with diabetes. If left untreated, periodontal disease in diabetic patients may lead to severe infection and even death. This study aimed to analyze factors influencing blood glucose levels and periodontal disease in patients with diabetes mellitus. It employed an observational analytic design with a cross-sectional approach, involving 30 diabetic respondents. Bivariate analysis revealed significant associations between stress level (p = 0.013) and periodontal disease (p = 0.004) with blood glucose levels (p < 0.05). The study concludes that stress level and periodontal disease are significantly related to blood glucose control in diabetic patients. It is recommended to provide greater attention through curative efforts, including non-pharmacological therapies such as relaxation techniques, diabetes exercise programs, and proper tooth-brushing education for patients with diabetes mellitus.